Comparing the given DE with
"aU_{xx} + 2bU_{xy} + cU_{yy}"
We have that
"a = 1, b=0, c = x"
But
"\\dfrac{dy}{dx} = \\dfrac{b \\pm \\sqrt{b^2-ac}}{a}"
In this case,
"\\dfrac{dy}{dx} = \\pm \\sqrt{-x}"
This value will be a real number since we are considering the region x < 0
"dy = \\pm (-x)^\\frac{1}{2}dx \\\\ y = \\pm \\dfrac{ 2(-x)^\\frac{3}{2}}{3} + c"
Set
"\\xi = 3y -2 (-x)^\\frac{3}{2} ....... (*)"
And
"\\eta = 3y + 2 (-x)^\\frac{3}{2}...... (**)"
"\\xi_x = -3(-x)^{\\frac{1}{2}} \\\\\n\\eta_x = 3(-x)^{\\frac{1}{2}}"
"\\xi_y = 3 \\\\ \\eta_y = 3"
"\\xi_{xx} =- \\frac{3}{2}(-x)^{-\\frac{1}{2}} \\\\\n\\eta_{xx}= \\frac{3}{2}(-x)^{-\\frac{1}{2}}"
"\\xi_{yy}= \\eta_{yy} = 0"
So we have that
"U_x = U_{\\xi} \\xi_x + U_{\\eta} \\eta_{x} = -3(-x)^{\\frac{1}{2}} U_{\\xi} + 3(-x)^{\\frac{1}{2}} U_{\\eta}"
"U_{xx} = -\\frac{3}{2}(-x)^{-\\frac{1}{2}} U_{\\xi}-9x U _{\\xi \\xi} + \\frac{3}{2}(-x)^{-\\frac{1}{2}} U_{\\eta}-9x U _{\\eta \\eta}"
"U_y = U_{\\xi} \\xi_y + U_{\\eta} \\eta_{y} = 3 U_{\\xi} + 3 U_{\\eta}"
"U_{yy} = 9U_{\\xi \\xi} + 3 U_{\\eta \\eta}"
From (*) and (**), we have that
"\\eta - \\xi = 4 (-x)^{\\frac{3}{2}} \\\\ (\\dfrac{4}{\\eta - \\xi})^ \\frac{1}{3} = (-x)^{-\\frac{1}{2}} .... (***)"
Substituting the value of "U_{xx}" and "U_{yy}" into the equation, we have
"U_{xx} + xU_{yy} = (U_{\\eta} - U_{\\xi}) \\frac{3}{2}(-x)^{-\\frac{1}{2}}"
And substituting (***), we have
"U_{xx}+xU_{yy} = \\dfrac{3(U_{\\eta} - U_{\\xi})}{[2(\\eta - \\xi)]^ \\frac{1}{3}}"
Comments
Leave a comment